2002
DOI: 10.1007/s00442-002-0951-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest fragmentation on the beetle assemblage at the relict forest of Fray Jorge, Chile

Abstract: Habitat fragmentation is recognized as one of the main factors associated with species extinction and is particularly acute in South American forest habitats. In this study, we examined the effects of forest fragmentation on the beetle assemblage at the relict temperate forest of Fray Jorge (Chile). We evaluated the following hypotheses: (1) there is a strong edge effect, so that the number of beetle species and individuals increases away from the edge, towards the inner part of each fragment, (2) this pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 41 publications
1
53
2
9
Order By: Relevance
“…The most common explanation for this trend is that there is a mixing of distinct fragment and matrix faunas at habitat edges, giving rise to a zone of overlap with greater overall species richness (Ingham & Samways, 1996;Magura, 2002). While this is the most general species richness pattern, it is by no means universal, as a number of studies have found either no edge effect for species richness (Davies & Margules, 1998;Mönkkönen & Mutanin, 2003) or a positive correlation (Davies, Melbourne & Margules, 2001 b ;Barbosa & Marquet, 2002;Bieringer & Zulka, 2003). Evidently, in some systems many species avoid edges and the matrix-dwelling fauna is not always speciose enough to compensate for the loss of species at edges (Fig.…”
Section: Edge Effects (1 ) Community Composition At Habitat Bounmentioning
confidence: 99%
“…The most common explanation for this trend is that there is a mixing of distinct fragment and matrix faunas at habitat edges, giving rise to a zone of overlap with greater overall species richness (Ingham & Samways, 1996;Magura, 2002). While this is the most general species richness pattern, it is by no means universal, as a number of studies have found either no edge effect for species richness (Davies & Margules, 1998;Mönkkönen & Mutanin, 2003) or a positive correlation (Davies, Melbourne & Margules, 2001 b ;Barbosa & Marquet, 2002;Bieringer & Zulka, 2003). Evidently, in some systems many species avoid edges and the matrix-dwelling fauna is not always speciose enough to compensate for the loss of species at edges (Fig.…”
Section: Edge Effects (1 ) Community Composition At Habitat Bounmentioning
confidence: 99%
“…In contrast to other studies (Didham et al 1998;Barbosa and Marquet 2001), the highest species richness was encountered in isolated forest fragments and old teak. Moreover, the similarity of arthropod assemblages was high, despite long distances among replicate sites (16-19 km).…”
Section: Edge Effects In Old Teak Plantations and Isolated Forest Fracontrasting
confidence: 99%
“…Forest fragmentation leads to the increase of forest edge in relation to forest core and it might have harsh consequences for most animals and plants (Fagan et al, 1999;Laurance and Yensen, 1991), changing their distribution, behaviour, and survival, due to habitat loss (Barbosa and Marquet, 2002;Murcia, 1995;Sartorius et al, 1999;Ishino et al, 2012). Such consequences may be evident up to 500m inside a forest fragment (Laurance, 1991;, but most of these effects are more obvious in the first 35m (Rodrigues, 1998) to 60m (Lovejoy et al, 1986).…”
Section: Introductionmentioning
confidence: 99%